Impact of Agricultural Land and the Output of Agricultural Products Moderated with Internet Users toward the Total export of Agricultural Product in Three Islamic South East Asian Countries - Akhmad Kusuma Wardhana; Ririn Tri Ratnasari (Department of Islamic Economic Law, Institut Agama Islam (IAI) Al-Qolam, 2022)
Agriculture was the key to preserving the main supply of food. Internet users could moderate the output of agricultural product. This study aims to explore and indepth analysis on the agricultural land and its products moderated with internet users could affect the total exports of agricultural materials in. This study used secondary data collected from sesric.org and fao.org from three OIC countries, Idonesia, Malaysia, and Brunei. This study used the number of internet users as a moderating variable on the effect of agricultural production which was divided into several types toward exports. The endogenous variable was total export, a moderating variable was the total of internet users, while the agricultural products were exogenous variables. The data were analyzed using moderated regression analysis to observe if the moderating variable affected exogenous variables. The result found that before the variables such as width of agricultural land, total output of cow’s meat, chicken’s meat, and freshwater fish were being moderated by number of internet users, all of them had no significant effect to total export.